Evaluation Of The In Vitro ⍺-Amylase Inhibitory, Antiglycation, And Antioxidant Properties Of Punica Granatum L. (Pomegranate) Fruit Peel Acetone Extract And Its Effect On Glucose Uptake And Oxidative Stress In Hepatocytes - Chukwuma, Chika, Ifeanyi.; Mashele, Samson, S.; Akuru, Eunice, Amaka. (Journal of Food Biochemistry Volume 44, Issue 5 e13175, 2020)
Punica granatum L. (pomegranate) is a widely eaten fruit. The antidiabetic, antioxidative, and antilipidemic properties of the hydroalcoholic extracts of the different plant's parts have been extensively studied, with scarce information on the acetone extract (ACE). This study investigated antidiabetic, antioxidative, and antiobesogenic properties of ACE of the fruit peel. Preliminary data showed that ACE showed stronger antioxidant (radical-scavenging IC50 = 1.56 μg/ml) and ⍺-amylase inhibitory (IC50 = 10.6 μg/ml) properties than the hydroalcoholic extracts and Acarbose. The ACE inhibited protein glycation and lipase activity. In hepatocytes, ACE impaired oxidative stress-induced lipid peroxidation and reduced glutathione depletion but increased glucose uptake without decreasing the cell viability. HPLC analysis showed predominant presence of bioactive phenolic acids (ferulic, caffeic, and gallic acids) in this extract. This study suggests that ACE of P. granatum fruit peel may be an understudied extract that contains potent antidiabetic and antioxidative bioactive principles with minimal toxicity. Practical applications Plant derived medicines have been an affordable and effective alternative therapy for many metabolic diseases, including diabetes. The fruit juice and fruits of pomegranate is widely consumed for the palatable taste and cardiovascular benefits. This study provides preliminary experimental evidences confirming that of the acetone extracts of pomegranate fruit peel, which has been sparsely studied, may possess more potent antidiabetic and antioxidative property than to the routinely studied hydroalcoholic counterparts. Additionally, the acetone extract is rich in bioactive phenolic acids, suggesting that the acetone extract of pomegranate fruit peel may be a promising candidate for further antidiabetic study and a source of bioactive principles for the management of diabetes and oxidative complications.
Article
Keywords: Acetone extract; Antidiabetic; Antioxidative; Fruit peel; High Performance Liquid Chromatography (HPLC); Pomegranate; Punica granatum L.